Aplikasi Pengenalan Tokoh Wayang Kulit dan Lagu Jawa Interaktif Berbasis Android - Aprianto, Dhoni, Dr. Ir. Banna Handaga, M.T (2016)
Puppet is the art of original culture in Indonesia. But, along the times, people choose modern culture and modern entertainment. In this era, almost people know entertainment, news, games, etc from mobile phone or smartphone. So, from this technology development, mobile phone can use as learning media. Through mobile phone we can learn a lot of knowledge. Not only news or education but from mobile phone we can also learn about puppet and java song. This application have purpose to help the user to learn puppet characters and java song easily, quickly and efficiently. The method of program development use SDLC (System Development Life Cycle) with Waterfall model that phases with needs analysis, design, coding, testing and analysis. This application was made by software Eclipse Juno to construct, database use SQLite, Sqlitebrowser for make database of java song, photoshop for photo editor. The result of the research is an application puppet android with size 12MB, version android min 2.3 (GingerBread) that show 149 characters of leather puppet to give information and knowledge about leather puppet like puppet pictures, names of puppet, family, siblings, characteristics, weapons and the other information about puppet characters. Then, for java song this application can show one song from 11 song type of Macapat with lyric and animation. So, lyric of song can show in one line according to the lyric displayed.